Expression differences of programmed death ligand 1 in de-novo and recurrent glioblastoma multiforme - Heynckes, Sabrina; Gaebelein, Annette; Haaker, Gerrit; Grauvogel, Jürgen; Franco, Pamela; Mader, Irina; Carro, Maria Stella; Prinz, Marco; Delev, Daniel; Schnell, Oliver; Heiland, Dieter Henrik (Oncotarget, 2017)
The biology of recurrent glioblastoma multiforme (GBM) is a dynamic process influenced by selection pressure induced by different antitumoural therapies. The poor clinical outcome of tumours in the recurrent stage necessitates the development of effective therapeutic strategies. Checkpoint-inhibition (PD1/PD-L1 Inhibition) is a hallmark of immunotherapy being investigated in ongoing clinical trials. The purpose of this study was to analyse the PD-L1 expression in de-novo and recurrent glioblastoma multiforme and to explore associated genetic alterations and clinical traits. We show that PD-L1 expression was reduced in recurrent GBM in comparison to de-novo GBM. Additionally, patients who received an extended dose of temozolomide (TMZ) chemotherapy showed a significantly reduced level of PD-L1 expression in the recurrence stage compared to the corresponding de-novo tumour. Our findings may provide an explanation for potentially lower response to immunotherapy in the recurrent stage due to the reduced expression of the therapeutic target PD-L1.
CRIS-Team Scopus Importer:2023-09-13
Keywords: GBM; Immune checkpoints; PD-L1; Recurrent GBM